FAKTOR PENYEBAB RENDAHNYA MOTIVASI INTRINSIK MAHASISWA DALAM MENYELESAIKAN SKRIPSI DI JURUSAN TEKNIK SIPIL FT UNP - 2063-2068, Dinda Amelia Rizki Pulungan (CIVED, 2018)
Abstract—This research started from many students have difficulty in completing thesis course.The purpose of this study describesfactors causing low intrinsic motivation of students in completing thesis in civil engineering department FT UNP. This research is a descriptive research population of students Prodi PTB force 2010, 2011 and 2012 in who are still active and have taken thesis subject in the semester of January-June 2017 as many as 69 respondents. The sample of research is determined by proportional random sampling formula as many as 59 respondents. Data were collected using questionnaires with Likert Scale consisting of 5 answers, consisting of positive and negative statements. Number of revelations on the questionnaire as many as 30 points.The results of this study indicate that the factors causing the low intrinsic motivation of students in completing the thesis are in the high category of 52.54%, with details of indicators as follows: 1) physical condition indicators are in the high category of 59.32%, 2) the psychological indicators are in the high category of 61.02% and 3) indicator of ideals are in very high category of 61.02%.Keywords:intrinsic factor, completing of thesis